The Effect of Computer-Based Resuscitation Simulation on Nursing Students' Performance, Self-Efficacy, Post-Code Stress, and Satisfaction. - Young Sook Roh; Sang Suk Kim (Research & Theory for Nursing Practice, 2014)
Computer-based simulation has intuitive appeal to both educators and learners with the flexibility of time, place, immediate feedback, and self-paced and consistent curriculum. The purpose of this study was to assess the effects of computer-based simulation on nursing students' performance, self-efficacy, post-code stress, and satisfaction between computer-based simulation plus instructor-led cardiopulmonary resuscitation training group and instructor-led resuscitation training-only group. This study was a nonequivalent control group posttest-only design. There were 213 second year nursing students randomly assigned to one of two groups: 109 nursing students with computer-based simulation or 104 with control group. Overall nursing students' performance score was higher in the computer-based simulation group than in the control group but reached no statistical significance (t = 1.086, p = .283). There were no significant differences in resuscitation-specific self-efficacy, post-code stress, and satisfaction between the two groups. Computer-based simulation combined with hands-on practice did not affect in nursing students' performance, self-efficacy, post-code stress, and satisfaction in nursing students. Further study must be conducted to inform instructional design and help integrate computer-based simulation and rigorous scoring rubrics.